THE RELATION BETWEEN TOURISM AND UNEMPLOYMENT: A PANEL DATA APPROACH - CONDRATOV, Iulian (Revista de turism - studii și cercetări în turism, 2017)
Tourism is one of the fastest growing sectors of the world economy. Tourism development may contribute to reduction of unemployment both directly and indirectly.  This paper empirically investigates this hypothesis holds for Romania regions for the period of 1990 -2015. A panel data approach is utilized and coefficient estimates are obtained by using fixed effect and random effect models. As a result, the hypothesis that tourism contribute to reduction of unemployment is verified based on the regression results.